1995
DOI: 10.1128/jvi.69.2.1160-1171.1995
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the trans-suppression activity of hepatitis C virus core protein by phosphorylation

Abstract: We previously demonstrated that the core protein of hepatitis C virus (HCV) can suppress gene expression and replication of hepatitis B virus (HBV) in a human hepatoma cell line (HuH-7). In this study, we have characterized the phosphorylation property of HCV core protein and examined the effect of phosphorylation on its suppressive activity of HBV. Our results indicated that both the full-length HCV core protein (22 kDa) and its processed or degraded forms (14 to 18 kDa) were phosphorylated in insect cells. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(59 citation statements)
references
References 63 publications
2
53
0
1
Order By: Relevance
“…S6 in the supplemental material), could be targeted individually or in combination for substitution and elucidation of any functional role. In any case, it seems likely that the SR-rich region of N is highly phosphorylated, as found in other viral systems, but this remains to be unambiguously estab- lished in MHV (58)(59)(60). It is noteworthy that this region of N also plays a significant electrostatic role in N-TRS RNA interactions (18); this suggests that TRS RNA binding and nsp3a binding might be mutually exclusive on N219 (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…S6 in the supplemental material), could be targeted individually or in combination for substitution and elucidation of any functional role. In any case, it seems likely that the SR-rich region of N is highly phosphorylated, as found in other viral systems, but this remains to be unambiguously estab- lished in MHV (58)(59)(60). It is noteworthy that this region of N also plays a significant electrostatic role in N-TRS RNA interactions (18); this suggests that TRS RNA binding and nsp3a binding might be mutually exclusive on N219 (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Finally, previous work suggests that HCV-mediated inhibition of HBV replication in patients coinfected with the two viruses most likely occurs through an HCV protein-mediated intracellular pathway (36). Studies in search of the HCV proteins that are responsible for the inhibition have reported that HCV core and NS2 proteins inhibited HBV replication in cultured cells, but so far, the underlined molecular mechanism(s) is not clear (9,12,38,43,44). Here we demonstrate that the HCV NS5A protein inhibits HBV gene transcription and DNA replication via the activation of the PI3K-Akt pathway and, thus may be, at least in part, responsible for the observed inhibition of HBV replication during HCV coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…"In vitro" studies have also revealed that HCV is capable of suppressing HBV replication, and this inhibitory effect is mediated by HCV core protein. [51][52][53][54] One study found the inhibitory effect of HCV was genotype-dependent, 53 being more pronounced in genotype 1 HCV infections. However, more research is needed before reaching a firm conclusion on this aspect.…”
Section: Viral Interactions Between Hbv and Hcvmentioning
confidence: 99%